The Interface Between International Intellectual Property and Environmental Protection: Biodiversity and Biotechnology - Charles R. McManis (Washington University Law Quarterly, 1998)
The Trade-Related Aspects of Intellectual Property Rights ("TRIPS") Agreement, part of the Final Act of the Uruguay Round of Multilateral Trade Negotiations, concluded on December 15, 1993. It seeks to strengthen international intellectual property protection in order to promote world trade. TRIPS also seeks to stimulate rapid international economic development that will likely produce a virtual technological transformation of human society and perhaps much of the natural world. In contrast, the United Nations Framework Convention on Biological Diversity ("Biodiversity Treaty"), concluded on June 5, 1992, in Rio de Janeiro, Brazil, seeks to preserve the natural world and maintain society's traditional, essentially agrarian, relationship to it. It also seeks to promote the concept of sustainable development. The debate over TRIPS and the Biodiversity Treaty has exposed a series of fault lines dividing technology-rich industrialized countries located in the temperate zone of the Northern Hemisphere, and the biodiversity-rich developing countries located primarily in the tropics and Southern Hemisphere. Part I of this Article will describe two of the most visible North- South conflicts, and Part II will examine the treaty provisions that have given rise to these conflicts. Part III will examine the two specific issues that are at the root of these North-South conflicts, and will conclude with a more cooperative vision of the interface between international intellectual property and environmental protection.
Keywords: Biodiversity; Intellectual property; International environmental law; Agreement on Trade-Related Aspects of Intellectual Property Rights